Multiple Radiocarbon Dating of Human remains: Clarifying the Chronology and Sequences of Burials in the late Neolithic Dolmen of Oberbipp (Switzerland). Issue 6 (22nd August 2019) - Steuri, Noah; Siebke, Inga; Furtwängler, Anja; Szidat, Sönke; Krause, Johannes; Lösch, Sandra; Hafner, Albert
ABSTRACT: Undisturbed megalithic burials are extremely rare because in addition to human activities, natural disturbances due to water influence and erosion or faunal activity are likely to occur over time. The dolmen of Oberbipp discovered in 2011 provides a unique opportunity for multidisciplinary research since anthropogenic and natural disturbances are minor. Morphological analysis indicates that approximately 42 individuals were buried in the grave chamber. Using archaeological methods alone, it would not have been possible to determine different occupation periods within the inhumations. Neolithic communities often reused dolmen over centuries. Therefore, radiocarbon ( 14 C) dating is the only method that can solve the question of temporal resolution. Fragments of the same bone element (right femora) were analyzed by two (in some cases three) different laboratories to date all inhumations individually. The aim of this study was threefold: (1) to determine the total occupation time of the dolmen (2) to evaluate the sequence of the burials, and (3) to compare the results of the same skeletal element from different laboratories. In total, 79 radiocarbon dating results from three different laboratories of the right femora (n = 32) were obtained. The total time span of the occupation of the dolmen was between 3350 and 2650 BC. The broad application of radiocarbon dating allowed the determination of two occupation periods within the burial.